Pengaruh Video Edukasi Terhadap Kemampuan Periksa Payudara Sendiri (SADARI) Pada Siswi SMA Setia Dharma Palembang - Dencik, Devina Anggrainy (Universitas Fort De Kock Bukittinggi, 2024)
Background: Breast cancer is the type of cancer that causes the highest number of deaths in the world. In 2020, global data shows that 2.3 million women were diagnosed with breast cancer. To reduce cancer cases and reduce cancer death rates, the government is implementing an early breast cancer detection program with BSE. The success of this program requires the right form of education. One thing that can be attempted is education using the video method. The aim of the research was to analyze the influence of educational videos on the BSE abilities of Setia Dharma High School students in Palembang. Methods: The research design used is quasi experimental pretest posttest woth control group, statistical tests namely paired t test and independent t test. Population: class X female students at Setia Dharma High School, a sample of 44 people taken with total sampling. The sample was divided into an intervention group (video education) and a control group (demonstration). Research results: the average in the educational video group before the intervention was 56.2 and the average after the intervention was 78.0. In the conventional demonstration group, the average score before intervention was 55.8 and after intervention was 74.8. The results of the paired sample t test obtained a p value <0.05, namely 0.002 in the educational video group and 0.004 in the conventional demonstration group. In the independent t test, the p value was 0.1 > 0.05. Conclusion: This shows that each intervention has an influence on the female students' ability to perform BSE and there is no significant difference between the video group and the demonstration group. It is recommended to continuously improve breast cancer prevention programs by intensively providing education about BSE.Keywords: BSE, breast cancer, adolescent girls